IMPROVEMENT OF ORGANIZATIONAL FORMS OF WORK OF THE LOCAL MEDICAL ORGANIZATION PROVIDING OUTPATIENT MEDICAL CARE - A.A. KALININSKAYA; I.М. SON; O.V. OBUKHOVA; L.A. BALZAMOVA; D.S. TERENTYEVA (Avicenna Tajik State Medical University, 2017)
Objective: Scientific substantiation of the organizational forms of the work of general medical practice in conditions of full fund holding of a medical organization that provides medical assistance on an outpatient medical care (MOOMC). Methods: The analysis of organizational forms of work and forms of financing of MOOMC was carried out. The following research methods were used: monographic, statistical, organizational experiment, direct observation. Results: Currently, in the condition of reforming primary health care (PHC), it is necessary to work out organizational and functional models of financing in a new quality under the experimental conditions, making them economically more efficient, sustainable and variable. The experiment of reforming of the outpatient clinic group in the Samara region, which included the transition to the provision of PHC to the urban population according to the principle of general medical practice, should be assessed as positive. At the same time, the general practitioner (GP), who possesses highly professional skills, is fully responsible for the health status of the adherent population and becomes a full fundholder. GP compensates for the volume of medical care that was provided to patients in hospitals, other medical organizations and ambulance teams. The introduction of financing with the full funding of the polyclinic link was accompanied by the improvement of the principles of organization and management of the service, the introduction of resource-saving technologies: day hospitals and inpatient hospitals, the organization of outpatient surgery centers, emergency medical care on the basis of MOOMC. Giving the GP the authority to independently manage financial resources significantly intensified the preventive work and affected the broad introduction of health schools. Conclusion: A mechanism has been created for the effective use of financial resources with the preservation of accessibility and provided the quality control of the medical care. The financing model in conditions of a full transition of a local polyclinic to a general medical practice with a fund holding should be recommended for implementation in other regions of the Russian Federation.